Favorable Outcomes after Implantation of Biodegradable Polymer Coated Sirolimus-Eluting Stents in Diabetic Population: Results from INDOLIMUS-G Diabetic Registry - Anurag Polavarapu; Raghava Sarma Polavarapu; Jayesh Prajapati; Asif Raheem; Kamlesh Thakkar; Shivani Kothari; Ashok Thakkar (International Journal of Vascular Medicine)
Objective. The main aim is to evaluate safety, efficacy, and clinical performance of the Indolimus (Sahajanand Medical Technologies Pvt. Ltd., Surat, India) sirolimus-eluting stent in high-risk diabetic population with complex lesions. Methods. It was a multicentre, retrospective, non-randomized, single-arm study, which enrolled 372 diabetic patients treated with Indolimus. The primary endpoint of the study was major adverse cardiac events (MACE), which is a composite of cardiac death, target lesion revascularization (TLR), target vessel revascularization (TVR), myocardial infarction (MI), and stent thrombosis (ST). The clinical follow-ups were scheduled at 30 days, 6 months, and 9 months. Results. The mean age of the enrolled patients was 53.4 ± 10.2 years. A total of 437 lesions were intervened successfully with 483 stents (1.1 ± 0.3 per lesion). There were 256 (68.8%) male patients. Hypertension and totally occluded lesions were found in 202 (54.3%) and 45 (10.3%) patients, respectively. The incidence of MACE at 30 days, 6 months and 9 months was 0 (0%), 6 (1.6%), and 8 (2.2%), respectively. The event-free survival at 9-month follow-up by Kaplan Meier method was found to be 97.8%. Conclusion. The use of biodegradable polymer coated sirolimus-eluting stent is associated with favorable outcomes. The results demonstrated in our study depict its safety and efficacy in diabetic population.